Detection of Mycobacterium tuberculosis in urine by Xpert MTB/RIF Ultra: A useful adjunctive diagnostic tool in HIV-associated tuberculosis. (October 2018) - Atherton, Rachel R.; Cresswell, Fiona V.; Ellis, Jayne; Skipper, Caleb; Tadeo, Kiiza K.; Mugumya, Gerald; Wadda, Vincent; Meya, David B.; Boulware, David R.
Highlights: Ultra has detected Mycobacterium tuberculosis in the urine of a patient with renal TB. Use of Xpert or Ultra on urine is not currently recommended due to lack of evidence. Urine Ultra may be useful in the diagnosis of extra-pulmonary TB in persons with HIV. Further study is required to characterise the diagnostic accuracy of urine Ultra. Abstract: In January 2017, the World Health Organisation recommended the Xpert ® MTB/RIF Ultra assay (Ultra) for tuberculosis (TB) diagnosis. Ultra offers improved analytical sensitivity when compared with the initial Xpert ® MTB/RIF (Xpert) assay for the detection of Mycobacterium tuberculosis . Ultra is therefore likely to be of particular benefit for detecting paucibacillary TB. We present a case from Uganda demonstrating Ultra positivity in urine from an HIV-infected patient presenting with altered mental status and urinary incontinence, and no other signs of active pulmonary or extrapulmonary TB. This represents the first published instance of a diagnosis of extrapulmonary TB made on the basis of a positive urine Ultra assay. The use of Ultra on urine may be a useful addition to the diagnostic armamentarium for disseminated TB in persons with HIV co-infection. The diagnostic accuracy of urine Ultra should be characterised further via prospective studies.